Environmental Law: A Study of Forest Governance Policy in Dompu District, West Nusa Tenggara - M. Yahya; Ridwan; Taufik Firmanto (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Forest governance has become a central issue in environmental law, particularly in regions vulnerable to deforestation and ecological degradation. Dompu District in West Nusa Tenggara, Indonesia, presents a critical case of forest area management where complex interactions between legal norms, institutional capacity, and community involvement shape the effectiveness of forest policies. This paper aims to analyze the implementation and challenges of forest governance in Dompu through the lens of environmental law. The study adopts a qualitative sociolegal methodology by examining statutory regulations, regional policies, and institutional roles, complemented by field interviews involving local government officials, environmental NGOs, forest rangers, and indigenous community representatives. The research reveals several systemic issues: overlapping legal jurisdictions, limited law enforcement capacity, insufficient public participation, and the marginalization of local wisdom in policy processes. Despite existing legal frameworks and conservation programs, unsustainable land use practices and weak coordination among stakeholders continue to hinder policy effectiveness. The findings suggest that reforming institutional structures, enhancing interagency coordination, and integrating traditional ecological knowledge into formal legal frameworks are essential steps toward improving forest governance. In conclusion, this paper contributes to the broader discourse on environmental legal reform and sustainable natural resource management by highlighting the local dynamics and legal complexities in the Dompu District context.